The Influence Of Green Marketing Towards Customer Loyalty Store Mustika Ratu Market - Ridho Rizka; Najmuddin; Nurfatehanny (Universitas Muhammadiyah Prof. DR HAMKA., 2020)
This study aims to examine the effect of Green Marketing on Customer Loyalty at Mustika Ratu Store Pasar Raya Blok M, South Jakarta. The population of this research is all Mustika Ratu customers who visit Pasar Raya Blok M, South Jakarta during the study period. The sample of this study was 40 Mustika Ratu customers taken using incidental sampling techniques. This research uses associative quantitative research methods. Based on the results of the linear regression calculation, it obtained Ῡ= 36.77 + 0.578 (x) and the ANAVA calculation results obtained Fvalue <Ftable (0.65, 2.19). Hypothesis testing was done by calculating the Pearson product moment correlation and it obtained rxy = 0.480. This shows the effect of green marketing on customer loyalty is Strong enough in accordance with the interpretation criteria in the Correlation Coefficient Interpretation Table namely 0.40 - 0.599. Therefore, the results of this study can be concluded that there is an influence of green marketing on customer loyalty.